Dynamic Budget-Total Need Based Resource Reservation Technique. Issue 2 (2nd April 2020) - Botlagunta, Madhavi Devi; Agrawal, Smriti; Rajeshwara Rao, R.
ABSTRACT: Contention for anything starts with common interest for it. Resources of common interest that must be exclusively held by a process at a time are commonly contested for in computing systems. This contention may lead to a deadlock among them. Several techniques in the literature exist for resource management with deadlock handling. The two major classes of such techniques namely; deadlock avoidance and resource reservation take steps for deadlock handling. However, both classes of techniques, work for only static systems, where system behavior is known in advance. The proposed technique aims to perform resource management with deadlock handling for a dynamic system. It proposes to use a dynamic budget that adjusts itself with the dynamic resource demands of the system. Safety tests are performed whenever this budget is modified to ensure that the system remains stable. The simulation results indicate the proposed technique has approximately 19% better average turnaround time. Graphical Abstract: uf0001